Anticoagulant therapy in orthopedic surgery – a review on anticoagulant agents, risk factors, monitoring, and current challenges - Yiqun Wang; Xiaobin Xu; Wei Zhu (Journal of Orthopaedic Surgery, 2024)
Orthopedic surgeries are associated with high-risk of thromboembolism which occurs in 40% to 60% of orthopedic patients in the absence of thromboprophylaxis. Conventionally heparin anticoagulants were used for thromboprophylaxis and currently direct oral anticoagulants (DOACs) are widely used due to their minimal complexity. Anticoagulant use carries bleeding risk and requires optimal laboratory monitoring through conventional thrombin-based assays, anti-Xa assay, anti-IIa assay and contemporary ecarin chromogenic assay (ECA) and rotational thromboelastometry. Monitoring requires multiple hospital visits and hence, the development of point-of-care assays is gaining momentum. Also, a thorough risk assessment model (RAM) is necessary for successful anticoagulant therapy since it enables personalized approach for better thromboprophylaxis outcomes. Despite welcoming changes, lack of guideline consensus, population-based thromboprophylaxis, deficiencies in risk stratification and non-adherence are still a concern. Stronger clinical and process support system with uniform guidelines approaches and patient-specific RAM can aid in the successful implementation of anticoagulant therapy.